tire
The tire design with a silica-rich rubber composition and micro-protuberances addresses sidewall crack resistance, improving durability and fuel efficiency by optimizing viscoelastic properties and reducing stress concentration.
Patent Information
- Application Number
- JP2023115443
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
AI Technical Summary
There is a need to improve the crack resistance of tire sidewalls to enhance tire durability and reduce environmental impact, while also considering fuel efficiency and weight optimization.
A tire design incorporating a rubber composition with a silica content of more than 20 parts by mass per 100 parts of rubber, along with specific viscoelastic properties and thickness relationships, combined with micro-protuberances on the sidewall surface, to enhance crack resistance and reduce stress concentration.
The proposed design significantly improves sidewall crack resistance, maintains flexibility and durability, and reduces weight, thereby enhancing tire performance and fuel efficiency.
Smart Images

Figure 2025012545000006 
Figure 2025012545000007 
Figure 2025012545000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a tire. [Background technology]
[0002] As the demand for fuel efficiency of tires increases, fuel efficiency is being considered not only in the tread portion of tires but also in other components such as sidewalls in order to improve the fuel efficiency of tires. For example, Patent Document 1 describes that fuel efficiency can be improved by using a rubber composition containing a specific resin in the sidewall of a tire. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-14506 Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, from the viewpoint of reducing the environmental impact, there is also a demand for further extending the life of tires, and there is room for improvement in terms of improving the crack resistance of the sidewall and further extending the life of the tires.
[0005] An object of the present invention is to improve the crack resistance of the sidewall. [Means for solving the problem]
[0006] The present invention relates to the following tire. A tire having a pair of sidewalls, the rubber composition constituting the sidewall contains a rubber component and silica, and the content of the silica is 20 parts by mass or more per 100 parts by mass of the rubber component; A tire in which 70°C tan δ, 70°C E*, and T satisfy the following relationship, where 70°C tan δ is the loss tangent (tan δ) of the rubber composition at 70°C, 70°C E* is the complex modulus (MPa) of the rubber composition at 70°C, and T is the thickness (mm) of the sidewall at the maximum width position of the tire. (1) 70℃tanδ<0.0253×T+0.083 (2) 70℃E*≦10.0 Effect of the Invention
[0007] According to the present invention, a tire having improved crack resistance in the sidewall can be provided. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a diagram showing a tire section width Wt, a tire section height Ht, a tire outer diameter Dt, and the like in a cross section of a tire. [Diagram 2] 1 is a schematic diagram of an outer surface of a sidewall having a plurality of columnar micro-ridges formed thereon. [Diagram 3] 1 is a schematic diagram of the outer surface of a sidewall on which a plurality of tiny pyramidal frustum-shaped protuberances are formed. [Figure 4] XX cross-sectional view of FIG. 3. [Diagram 5] 1 is a schematic diagram of an outer surface of a sidewall having a plurality of rib-like micro-ridges formed thereon. [Figure 6] 6 is a cross-sectional view taken along the line YY in FIG. 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention relates to the following tire. A tire having a pair of sidewalls, the rubber composition constituting the sidewall contains a rubber component and silica, and the content of the silica is 20 parts by mass or more per 100 parts by mass of the rubber component; A tire in which 70°C tan δ, 70°C E*, and T satisfy the following relationship, where 70°C tan δ is the loss tangent (tan δ) of the rubber composition at 70°C, 70°C E* is the complex modulus (MPa) of the rubber composition at 70°C, and T is the thickness of the sidewall at the maximum width position of the tire (mm). (1) 70℃tanδ<0.0253×T+0.083 (2) 70℃E*≦10.0
[0010] Although it is not intended to be bound by theory, the following mechanism is considered to improve the crack resistance of the sidewall in the present invention. That is, first, (1) the sidewall deforms during rolling, and the accumulation of deformation makes it easy for cracks to occur. Therefore, the complex elastic modulus of the sidewall rubber is set to a predetermined value or less to make it soft. This allows flexible deformation against strain generated on the surface, and it is considered that the occurrence of cracks is suppressed. In addition, (2) the higher the loss tangent tan δ of the sidewall rubber, the higher the temperature rises due to deformation during rolling, the lower the fracture properties, and the more likely cracks are to occur. Therefore, the tan δ is made small according to the thickness of the sidewall rubber. As a result, when the thickness of the sidewall rubber is thick, the rigidity of the sidewall is ensured to suppress deformation, and when the thickness of the sidewall rubber is thin, the heat generation due to deformation is suppressed, making it easier to suppress temperature rise in the sidewall, and it is considered that a high fracture property is maintained. Furthermore, (3) as a filler, silica is less likely to bind the surrounding polymer than carbon black. For this reason, it is believed that compounding a certain amount of silica improves the elongation at break and increases the flexibility of the rubber, thereby suppressing the occurrence of cracks. It is believed that the above (1) to (3) work together to provide high crack resistance.
[0011] The rubber composition contains carbon black, and the content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is A SIL The carbon black content (parts by mass) is A CB Then, ASIL and A CB It is preferable that the following relationship is satisfied: (3) A CB / A SIL <= 1
[0012] By incorporating a large amount of silica as a filler, the silica's characteristic of being less likely to bind surrounding polymers than carbon black is brought to bear, which is thought to contribute to improved crack resistance.
[0013] The rubber composition contains carbon black, and the carbon black preferably contains recovered carbon black (rCB).
[0014] Because the surface of the rCB is burned, the bonds with the surrounding rubber molecules tend to be slightly weaker. This makes it easier for the surrounding rubber molecular chains to release force when the tire is deformed, which is thought to contribute to improving the crack resistance of the sidewall.
[0015] The silica preferably contains silica having an average primary particle size of 16 nm or less.
[0016] By incorporating silica with a smaller particle size, heat generation due to friction between silica particles is reduced, the temperature rise in the sidewall can be suppressed, and excellent fracture properties can be maintained, which is thought to improve crack resistance.
[0017] When the tire weight (kg) of the tire is G and the maximum load capacity (kg) of the tire is WL, it is preferable that G and WL satisfy the following relationship. (4) G / WL≦0.0180
[0018] The maximum load capacity of a tire is a value proportional to the virtual volume of the tire. Therefore, by increasing the maximum load capacity relative to the tire weight, the tire as a whole can be made thinner, improving the heat dissipation effect, which is thought to contribute to improving crack resistance.
[0019] At least one of the pair of side walls preferably has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface thereof.
[0020] The presence of the micro-ridges can suppress stress concentration on the outer surface of the sidewall, which is believed to contribute to improving the crack resistance of the sidewall.
[0021] The shape of the minute protuberances is preferably columnar, frustum or rib-like.
[0022] By providing the micro-ridges with these predetermined shapes, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0023] The micro-ridges have a height of 0.03 mm or more and 0.50 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge formation portion is 2 It is preferable that the area is equal to or larger than this.
[0024] By having the size of the micro-protuberances fall within these prescribed ranges, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0025] The maximum width of the minute protuberances is preferably 0.03 mm or more and 5.0 mm or less.
[0026] By having the maximum width of the micro-protuberances fall within a prescribed range, stress concentration on the outer surface of the sidewall can be suppressed, which is believed to contribute to improving the crack resistance of the sidewall.
[0027] It is preferable that the height of the minute protuberances gradually increases from the maximum tire width position toward the outside in the tire radial direction, and gradually increases from the maximum tire width position toward the inside in the tire radial direction.
[0028] Relatively large distortion occurs near the sidewall at the widest point of the tire, but by making the height of the micro-bumps lower on the side closer to the widest point of the tire, it is believed that this reduces the unevenness in the rubber volume in the circumferential direction of the tire at the point where large distortion occurs, avoids stress concentration near the micro-bumps, and contributes to improving the crack resistance of the sidewall.
[0029] <Definition> "Normal condition" refers to a condition where the tire is mounted on a normal rim, inflated to normal internal pressure, and unloaded. "Dimensions, etc. of each part of the tire" are values specified in the normal condition, unless otherwise specified.
[0030] "Genuine rim" refers to a rim that is specified for each tire by the standard system that includes the standard on which the tire is based, for example, the standard rim for the applicable size listed in the "JATMA YEAR BOOK" for JATMA (Japan Automobile Tire Manufacturers Association), the "Measuring Rim" listed in the "STANDARDS MANUAL" for ETRTO (The European Tyre and Rim Technical Organisation), and the "Design Rim" listed in the "YEAR BOOK" for TRA (The Tire and Rim Association, Inc.), referring to JATMA, ETRTO, and TRA in that order, and following the standard if there is an applicable size at the time of reference. And, for tires not specified in the standard, it refers to a rim that can be assembled to a rim and can hold internal pressure, that is, a rim that does not leak air from between the rim and tire, with the smallest rim diameter and the next narrowest rim width.
[0031] "Regular internal pressure" refers to the air pressure set for each tire by each standard in the standard system including the standard on which the tire is based. For JATMA, it is the "maximum air pressure", for ETRTO, it is "INFLATION PRESSURE", and for TRA, it is the "maximum value" listed in the table "TIRE LOAD LIMITS AT VARIOUS COLD INFLATION PRESSURES". As with regular rims, refer to JATMA, ETRTO, and TRA in that order, and follow the standard if there is an applicable size at the time of reference. In the case of a tire not specified in the standard, it refers to the regular internal pressure (250KPa or more) of another tire size (specified in the standard) that is specified with the regular rim as the standard rim. Note that if multiple regular internal pressures of 250KPa or more are listed, it refers to the smallest value among them.
[0032] "Tire weight (G) (kg)" is the weight of the tire itself, excluding the weight of the rim. In addition, if sound-deadening material, sealant, sensors, etc. are attached to the tire cavity, G is the value including the weight of these items.
[0033] "Maximum load capacity (WL) (kg)" is a value calculated by the following formulas (A) and (B) when the tire section width, tire section height, and tire outer diameter measured under normal conditions are Wt (mm), Ht (mm), and Dt (mm), respectively. V is the virtual volume of the space occupied by the tire. The tire section width Wt is the maximum width between the outer surfaces of the sidewalls under normal conditions, excluding patterns or letters, if any, on the tire side. The tire section height Ht is the distance from the bottom surface of the bead to the outermost surface of the tread, and is half the difference between the tire outer diameter Dt and the rim diameter R (mm). V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt (A) WL=0.000011×V+100 (B)
[0034] "Sidewall thickness (T) (mm)" refers to the thickness (mm) of the rubber that constitutes the sidewall, measured along the normal line L of the tire's maximum width position PW of the sidewall. "Tire's maximum width position PW" refers to the position on the sidewall surface where the tire's cross-sectional width Wt is measured. T is measured with the tire cut on a plane passing through the tire's rotational axis and placed on a standard rim.
[0035] The term "micro-ridge" refers to a convex protuberance having a height of 0.03 mm to 5.0 mm formed on the outer surface of the sidewall. The maximum width of the micro-ridge is preferably 0.03 mm to 5.0 mm.
[0036] The "microridge formation portion" refers to the portion on the outer surface of the sidewall where the microridges are formed.
[0037] "Recovered carbon black" refers to carbon black obtained from the pyrolysis process of products such as used tires that contain carbon black, and which, when subjected to oxidative combustion by heating in air in a thermogravimetric measurement method conforming to JIS K 6226-2:2003, has a mass ratio of ash (ash content), which is a component that does not burn, of 13 mass% or more. In other words, the mass (carbon content) of the part lost due to the oxidative combustion is 87 mass% or less. Recovered carbon black is sometimes expressed as rCB.
[0038] The "plasticizer content" includes the amount of plasticizer in the rubber component extended by the plasticizer. Similarly, the "oil content" includes the amount of oil contained in the oil-extended rubber.
[0039] <Measurement method> "Styrene content" is 1 It is calculated by H-NMR measurement.
[0040] The "vinyl bond content (1,2-bonded butadiene unit content)" is measured by infrared absorption spectroscopy.
[0041] The "cis content (amount of cis-1,4-bonded butadiene units)" is measured by infrared absorption spectroscopy.
[0042] The "weight average molecular weight (Mw)" can be determined by converting the measured value obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMALTPORE HZ-M manufactured by Tosoh Corporation) into a standard polystyrene equivalent.
[0043] "N2SA of carbon black" is a value determined by JIS K 6217-2:2017.
[0044] "N2SA of Silica" is a value measured by the BET method in accordance with ASTM D3037-93.
[0045] The "average primary particle size" is calculated by photographing particles with a transmission or scanning electron microscope and taking the arithmetic average of the particle sizes of 400 particles. If the particle shape is nearly circular, the diameter of the circle is used as the particle size, if it is needle-like or rod-like, the short diameter is used as the particle size, and in other cases, the equivalent circle diameter is calculated from the electron microscope image. The equivalent circle diameter is calculated as "4 x (particle area) / positive square root of π". The average primary particle size is applied to silica, carbon black, etc.
[0046] "Softening point of resin, etc." means the temperature at which the ball drops when the softening point as specified in JIS K 6220-1:2015 is measured using a ring and ball softening point tester, unless otherwise specified. Softening points measured by other methods are noted accordingly.
[0047] "70℃ tan δ" is measured using a GABO Iplexer series under the following conditions: temperature 70℃, initial strain 10%, dynamic strain ±1%, frequency 10Hz, and elongation mode. When taking samples from tires, take samples of length 20mm x width 4mm x thickness 1mm from inside the rubber layer of the sidewall of each test tire, with the tangential direction in the tire circumferential direction as the long side and the tire width direction as the thickness.
[0048] "70℃E*" is the complex modulus (MPa) measured using a GABO Iplexer series under the conditions of temperature 70℃, initial strain 10%, dynamic strain ±1%, frequency 10Hz, and elongation mode. When taking samples from tires, the same procedure is used as for 70℃ tan δ.
[0049] <Tires> The tire of the present invention will be described below with reference to the drawings as appropriate. However, the drawings are merely examples for the purpose of explanation.
[0050] The tire of the present invention is a tire in which the rubber composition constituting the sidewall contains 20 parts by mass or more of silica per 100 parts by mass of the rubber component, and the 70°C tan δ and 70°C E* (MPa) of the rubber composition and the thickness T (mm) of the sidewall at the maximum width position of the tire satisfy the predetermined relationships represented by the above formula (1) and formula (2).
[0051] Fig. 1 is a cross-sectional view of a tire having a pair of sidewalls, taken along a plane passing through the tire rotation axis. In Fig. 1, Wt indicates the tire section width, Ht indicates the tire section height, and Dt indicates the tire outer diameter. As shown in Fig. 1, the thickness T of the sidewall is the thickness of the rubber constituting the sidewall, measured along a normal line L of the tire maximum width position PW of the sidewall. Here, the tire maximum width position PW is the position on the outer surface of the sidewall where the tire section width Wt is measured.
[0052] (Formula (1)) The relationship satisfied by formula (1) is as follows. (1) 70℃tanδ<0.0253×T+0.083
[0053] In formula (1), the difference obtained by subtracting the value on the left side from the value on the right side is preferably greater than 0.010, more preferably greater than 0.020, even more preferably greater than 0.030, even more preferably greater than 0.040, even more preferably greater than 0.050, even more preferably greater than 0.060, and even more preferably greater than 0.070.
[0054] The 70°C tan δ is preferably less than 0.130, more preferably less than 0.120, even more preferably less than 0.115, even more preferably 0.112 or less, and even more preferably less than 0.110. There is no particular restriction on the lower limit of the 70°C tan δ from the viewpoint of the effects of the invention, but for example, it is preferably 0.020 or more, more preferably 0.030 or more, and even more preferably 0.050 or more.
[0055] The 70°C tan δ of the rubber composition can be adjusted appropriately by the type and amount of the components constituting the rubber composition described below. For example, there is a tendency that the 70°C tan δ can be increased by increasing the amount of the filler, decreasing the particle size thereof, decreasing the amount of the vulcanizing agent and vulcanization accelerator, etc. Therefore, there is a tendency that the 70°C tan δ can be decreased by the reverse operation.
[0056] The thickness T (mm) of the sidewall is not particularly limited as long as it is within the range of thickness that can be normally adopted. For example, in the case of a passenger car tire, T is preferably more than 1.0 mm, more preferably more than 1.5 mm, and even more preferably 2.0 mm or more. On the other hand, T is preferably less than 10.0 mm, more preferably less than 9.0 mm, even more preferably 8.0 mm or less, even more preferably 7.0 mm or less, and even more preferably 6.0 mm or less.
[0057] (Formula (2)) The relationship satisfied by equation (2) is as follows. (2) 70℃E*≦10.0
[0058] The value of the right side of formula (2) is preferably 8.0, more preferably 6.0, even more preferably 5.0, even more preferably 4.7, even more preferably 4.1, even more preferably 4.0, even more preferably 3.6. There is no particular lower limit for the 70°C E* value from the viewpoint of the effects of the present invention, but it may be, for example, 2.0 or 3.0.
[0059] The 70°C E* of the rubber composition can be adjusted appropriately by the type and amount of the components constituting the rubber composition described below. For example, there is a tendency that the 70°C E* can be increased by increasing the amount of the filler, decreasing the particle size thereof, decreasing the total amount of the plasticizer, and increasing the amount of the vulcanizing agent and vulcanization accelerator. Therefore, there is a tendency that the 70°C E* can be decreased by the reverse operation.
[0060] (Formula (3)) The relationship that formula (3) satisfies is as follows. This point will be described in the explanation of the filler. (3) A CB / A SIL <= 1
[0061] (Formula (4)) The relationship satisfied by equation (4) is as follows. (4) G / WL≦0.0180
[0062] The tire of the present invention that satisfies the above formula (4) is a tire that has a relatively large maximum load capacity relative to the tire weight. The right side of formula (4) is preferably 0.0170, more preferably 0.0165, and even more preferably 0.0161. On the other hand, the lower limit of G / WL is not particularly limited from the viewpoint of the effects of the present invention, but a reference value is, for example, about 0.0120.
[0063] The value of G / WL can be decreased by decreasing the value of G relative to the value of WL, and conversely, it can be increased by increasing the value of G relative to the value of WL.
[0064] As described above, WL is a value determined according to the tire section width Wt (mm), tire section height Ht (mm), and tire outer diameter Dt (mm). Figure 1 shows the Wt, Ht, and Dt of a tire.
[0065] (Minor ridge formation part) The tire of the present invention preferably has a microridge-forming portion in which a plurality of microridges are formed on the outer surface of at least one of the pair of sidewalls.
[0066] In the microridge formation portion, the microridges may be in a single row in the radial direction of the tire, or in multiple rows. Here, "a single row in the radial direction of the tire" means that there are not two or more microridges lined up in the radial direction of the tire. Also, the microridges may be in a single row in the circumferential direction of the tire, or in multiple rows. Here, "a single row in the circumferential direction of the tire" means that there are not two or more microridges lined up in the circumferential direction of the tire. It is preferable that the microridges are provided in multiple rows in the radial direction of the tire and multiple rows in the circumferential direction of the tire.
[0067] The area of the micro-ridge formation is the area defined by a line encircling the outermost part of the multiple micro-ridges arranged at intervals of 0.50 mm or less when viewed from a direction perpendicular to the tire surface. The area of the micro-ridge formation is 10 mm 2 It is preferable that the micro-ridge forming portion is equal to or larger than the above because this can suppress stress concentration on the outer surface of the sidewall and contribute to improving the crack resistance of the sidewall. Furthermore, in the micro-ridge forming portion, the group of micro-ridges may be continuous or may be divided. Here, divided means that the spacing between the micro-ridges is greater than 1.0 mm. Therefore, it is sufficient that there is at least one micro-ridge forming portion on the outer surface of at least one of the pair of sidewalls, and there may be multiple micro-ridge forming portions.
[0068] (minor elevation) The shape of the micro-ridge is not particularly limited as long as it suppresses stress concentration on the outer surface of the sidewall and contributes to improving the crack resistance of the sidewall, and specifically includes a columnar shape, a frustum shape, a rib shape (striped shape), etc. Examples of the columnar shape include a cylindrical shape and a polygonal prism shape such as a triangular prism shape, a square prism shape, and a pentagonal prism shape. Examples of the frustum shape include a circular frustum shape and a polygonal prism shape such as a triangular frustum shape, a square frustum shape, and a pentagonal frustum shape. Examples of the rib shape include a cross-sectional shape perpendicular to the longitudinal direction of the rib-shaped micro-ridge, and any shape may be included. Examples of the cross-sectional shape include a rectangle or a trapezoid.
[0069] FIG. 2 shows a part of the microridge formation part in which a cylindrical microridge 2 is formed on the sidewall outer surface 1. FIG. 3 shows a part of the microridge formation part in which a square pyramidal truncated microridge 3 is formed on the sidewall outer surface 1. FIG. 4 is an XX cross-sectional view of FIG. 3, and is a view of the microridges viewed from a direction perpendicular to a plane including a normal line to the sidewall outer surface. FIG. 4 shows the height h of the microridges 3, the maximum width w of the microridges 3, and the interval d of the microridges 3. FIG. 5 shows a part of the microridge formation part in which rib-shaped microridges 4 are formed on the sidewall outer surface 1. FIG. 6 is a YY cross-sectional view of FIG. 5, and is a view of the microridges viewed from a direction perpendicular to a plane including a normal line to the sidewall outer surface. FIG. 6 shows the height h of the microridges 4, the maximum width w of the microridges 4, and the interval d of the microridges 4.
[0070] Here, with respect to the microridges, "height" refers to the maximum height of the microridges measured along a normal line erected on the outer surface of the sidewall, "maximum width" refers to the maximum width of the microridges on the outer surface of the sidewall measured in one direction in which the microridges are arranged, and "spacing" refers to the minimum spacing of the microridges on the outer surface of the sidewall measured in one direction in which the microridges are arranged. Note that the height, maximum width, and spacing of the microridges are all measured with the outer surface of the sidewall developed on a plane.
[0071] The height of the microbumps at the maximum tire width position is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more, while the height is preferably 0.50 mm or less, may be 0.45 mm or less, or may be 0.40 mm or less. The maximum width of the microbumps is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more, while the maximum width is preferably 5.00 mm or less, may be 3.00 mm or less, may be 1.00 mm or less, or may be 0.50 mm or less. Furthermore, the spacing between the microbumps is preferably 1.00 mm or less, may be 0.70 mm or less, or may be 0.50 mm or less. The spacing between the microbumps may be at least about half the maximum width, and may be about the same as the maximum width. The density of the microbumps (pieces / cm 2 ) can be roughly calculated from the maximum width and interval of the micro-ridges. For example, in the case of the examples described later, it is about 700 pieces / cm 2 It is.
[0072] It is preferable that 20 or more micro-ridges are formed in at least one direction, because this can suppress stress concentration on the outer surface of the sidewall and contribute to improving the crack resistance of the sidewall.
[0073] It is preferable that the height of the micro-ridges gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and also gradually increases from the maximum tire width position toward the inner side in the tire radial direction. This is because, although relatively large distortion occurs near the maximum tire width position of the sidewall, by making the height of the micro-ridges lower on the side closer to the maximum tire width position, it is believed that this reduces the non-uniformity of the rubber volume in the tire circumferential direction at the position where large distortion occurs, avoids stress concentration near the micro-ridges, and contributes to improving the crack resistance of the sidewall.
[0074] It is preferable that the microridge has an arc-shaped recess on the outermost surface of the microridge, as in the microridge 4 shown in Fig. 5. This is because such a configuration can prevent air from accumulating in the arc-shaped recess, thereby preventing poor appearance of the microridge.
[0075] <Rubber composition> The rubber composition constituting the sidewall of the tire of the present invention will be described. The rubber composition contains a rubber component and silica, and the content of the silica is 20 parts by mass or more per 100 parts by mass of the rubber component, and may further contain other compounding ingredients.
[0076] (Rubber component) The rubber component preferably contains at least one diene rubber component selected from the group consisting of isoprene rubber (IR rubber), styrene butadiene rubber (SBR), and butadiene rubber (BR). The rubber component may contain at least two rubber components selected from the group consisting of IR rubber, SBR, and BR, or may contain IR rubber, SBR, and BR. Of these, the rubber component preferably contains IR rubber and BR, and may consist of only IR rubber and BR. These rubber components may be extended rubbers extended with a plasticizer described later, or may be rubbers that have been modified or hydrogenated by adding hydrogen to double bonds.
[0077] <Isoprene rubber> Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, modified IR, etc. As NR, for example, SIR20, RSS♯3, TSR20, etc., which are common in the tire industry, can be used. As IR, there is no particular limitation, and for example, IR2200, etc., which are common in the tire industry can be used. As modified NR, deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), etc., as modified NR, epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), grafted natural rubber, etc., as modified IR, epoxidized isoprene rubber, hydrogenated isoprene rubber, grafted isoprene rubber, etc. can be used. These may be used alone or in combination of two or more.
[0078] The content of the isoprene-based rubber in 100% by mass of the rubber component is preferably more than 20% by mass, more preferably more than 30% by mass, even more preferably more than 40% by mass, and even more preferably 45% by mass or more from the viewpoint of improving the breaking elongation and crack resistance of the rubber composition, while it is preferably less than 75% by mass, more preferably less than 65% by mass, and even more preferably less than 55% by mass from the viewpoint of suppressing deterioration due to heat, etc.
[0079] ≪SBR≫ There are no particular limitations on the SBR, and for example, emulsion-polymerized styrene-butadiene rubber (E-SBR), solution-polymerized styrene-butadiene rubber (S-SBR), etc. can be used. The SBR may be unmodified or modified. Hydrogenated styrene-butadiene copolymer (hydrogenated SBR) can also be used as the SBR. These may be used alone or in combination of two or more.
[0080] The styrene content of SBR is preferably more than 5.0 mass%, more preferably more than 7.5 mass%, and even more preferably 10.0 mass% or more. The styrene content is preferably less than 40.0 mass%, more preferably less than 35.0 mass%, and even more preferably less than 30.0 mass%. By keeping it within the above range, it is believed that micro styrene domains can be formed in the rubber component, making it easier to absorb strain due to deformation in the rubber composition. In this specification, the styrene content is defined as 1 It can be measured by H-NMR measurement.
[0081] The vinyl bond content of SBR is preferably more than 5 mol%, more preferably more than 10 mol%, and even more preferably more than 15 mol%. The vinyl bond content is preferably less than 65 mol%, more preferably less than 60 mol%, and even more preferably less than 50 mol%. The vinyl bond content can be measured by the above-mentioned method.
[0082] As the SBR, SBR extended with a plasticizer (extended SBR) can be used, or non-extended SBR can be used. When extended SBR is used, the amount of extension of SBR, i.e., the content of the extended plasticizer contained in SBR, is preferably 10 to 50 parts by mass per 100 parts by mass of the rubber solid content of SBR. Examples of the plasticizer used for extension include resins, oils, liquid polymers, and ester-based plasticizers, which will be described later.
[0083] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.
[0084] The content of SBR in 100% by mass of the rubber component may be 0% by mass, but may be, for example, more than 1% by mass, more than 5% by mass, or more than 10% by mass. The upper limit of the SBR content is preferably less than 40% by mass, more preferably less than 35% by mass, and further preferably 30% by mass or less.
[0085] The BR is not particularly limited, and examples of the BR that can be used include high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. These may be used alone or in combination of two or more.
[0086] In particular, the BR preferably contains high-cis BR having a cis content of more than 90% by mass. The cis content is more preferably more than 95% by mass, and more preferably 98% by mass or more. The cis content can be measured by the above-mentioned method.
[0087] The BR may be unmodified or modified. The modified BR may be modified BR having the same functional group as the modified diene rubber. The BR may be a hydrogenated butadiene polymer (hydrogenated BR).
[0088] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.
[0089] From the viewpoints of fuel economy and crack growth resistance, the content of BR in 100% by mass of the rubber component is preferably more than 20% by mass, more preferably 25% by mass or more, even more preferably more than 30% by mass, even more preferably more than 35% by mass, even more preferably more than 40% by mass, even more preferably more than 45% by mass, even more preferably more than 50% by mass, and even more preferably 55% by mass or more. On the other hand, the upper limit is preferably less than 75% by mass, more preferably less than 70% by mass, and even more preferably less than 65% by mass.
[0090] <Other rubber components> As the rubber component, rubbers other than those mentioned above can be used. Examples of rubbers other than those mentioned above include diene rubbers such as styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR), and non-diene rubbers such as ethylene propylene diene rubber (EPDM), butyl rubber (IIR), and halogenated butyl rubber (X-IIR). These may be used alone or in combination of two or more.
[0091] The content of the diene rubber in 100% by mass of the rubber component is preferably more than 80% by mass, more preferably more than 90% by mass, and most preferably 100% by mass.
[0092] (Filler) The rubber composition constituting the sidewall according to the present invention contains 20 parts by mass or more of silica per 100 parts by mass of the rubber component. The silica has a nitrogen adsorption specific surface area (N2SA) of 180 m 2 It is preferable that the silica content is 180m / g or more. 2 The rubber composition constituting the sidewall according to the present invention may be composed only of silica having a silica content of at least 100% by mass per unit area (g / g). The rubber composition constituting the sidewall according to the present invention preferably contains carbon black (CB), and the carbon black preferably contains recovered carbon black (rCB).
[0093] <Silica> As the silica, dry process silica (anhydrous silica), wet process silica (hydrated silica), etc. can be used. Among them, wet process silica is preferred because it has a large number of silanol groups. As commercially available products, products from Degussa, Rhodia, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Corporation, etc. can be used. These may be used alone or in combination of two or more kinds. In addition to these silicas, silica made from biomass materials such as rice husks can also be used.
[0094] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g, more preferably 100m 2 / g, more preferably 150m 2 / g, more preferably 175m 2 / g or more, more preferably 180m 2 / g or more, more preferably 190m 2 / g, more preferably 200m 2 / g, more preferably 210m 2 / g, more preferably 220m 2 / g, more preferably 230m 2 / g, more preferably 235m 2 The upper limit of the N2SA of silica is not particularly limited, but is preferably 600 m 2 / g, more preferably less than 350 m2 / g, and even more preferably less than 300 m 2 / g. By setting it within the above range, there is a tendency for crack propagation resistance to be improved. The N2SA of silica is a value measured by the above-mentioned method.
[0095] From the viewpoint of reinforcing property, low fuel consumption, etc., the average primary particle size of silica is preferably less than 25 nm, more preferably less than 22 nm, even more preferably less than 20 nm, even more preferably less than 18 nm, even more preferably 17 nm or less, even more preferably 16 nm or less, even more preferably less than 16 nm, even more preferably 15 nm or less. The lower limit of the average primary particle size is not particularly limited, but is preferably more than 3 nm, more preferably more than 5 nm, even more preferably more than 10 nm. The average primary particle size of silica can be determined by the above-mentioned method.
[0096] Carbon Black (CB) The carbon black is not particularly limited, and any carbon black that can be used in the tire industry can be used. Examples of such carbon black include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, N660, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin-Nichika Carbon Co., Ltd., and Columbia Carbon Co., Ltd. In addition, from the viewpoint of environmental load and from the viewpoint of reducing friction between the carbon black surface and rubber molecular chains and suppressing heat generation, recovered carbon black (rCB) obtained by pyrolysis of used tires may be used. These may be used alone or in combination of two or more.
[0097] Recovered carbon black can be obtained from the pyrolysis process of used pneumatic tires. For example, European Patent Application Publication No. 3427975, referring to "Rubber Chemistry and Technology", Vol. 85, No. 3, pp. 408-449 (2012), in particular pp. 438, 440, and 442, describes that recovered carbon black can be obtained by pyrolysis of organic materials at 550-800°C with the exclusion of oxygen, or by vacuum pyrolysis at relatively low temperatures (
[0027] ). Carbon black obtained from such pyrolysis processes usually lacks functional groups on its surface, as mentioned in
[0004] of Japanese Patent No. 6856781 (Comparison of Surface Morphology and Chemistry of Pyrolytic Carbon Black and Commercial Carbon Black, Powder Technology 160 (2005) 190-193).
[0098] The recovered carbon black preferably lacks functional groups on its surface, but may contain functional groups on its surface, or may be treated to contain functional groups on its surface, as long as the effect of the present invention is not affected. The treatment to contain functional groups on the surface of the recovered carbon black can be carried out by a conventional method. For example, in European Patent Application Publication No. 3173251, carbon black obtained from a pyrolysis process is treated with potassium permanganate under acidic conditions to obtain carbon black containing hydroxyl and / or carboxyl groups on its surface. In Japanese Patent No. 6856781, carbon black obtained from a pyrolysis process is treated with an amino acid compound containing at least one thiol group or disulfide group to obtain carbon black with an activated surface. The recovered carbon black according to the present embodiment also includes carbon blacks treated to contain functional groups on their surfaces.
[0099] As the recovered carbon black, commercially available products from Strable Green Carbon, LD Carbon, etc. can be used.
[0100] The average primary particle size of carbon black is preferably more than 20 nm, more preferably more than 25 nm, even more preferably more than 30 nm, and particularly preferably more than 35 nm. By setting the average primary particle size of carbon black within the above range, the rubber molecules bound by carbon black are minimized and become more flexible, so that it is considered that the polymer molecular chain can relax the stress against the input and suppress the occurrence of cracks. On the other hand, from the viewpoint of obtaining reinforcing properties, the average primary particle size is preferably less than 90 nm, more preferably less than 85 nm, and even more preferably 80 nm or less. The average primary particle size of carbon black is measured by the above-mentioned measurement method.
[0101] From the viewpoint of the effect of the present invention, the nitrogen adsorption specific surface area (N2SA) of carbon black is 90 m 2 / g is preferable, and 80m 2 / g is more preferable, and 70m 2 / g is more preferable, and 60m 2 / g is particularly preferred. 2 / g or more is preferable, and 20m 2 More preferably, 30m 2 More preferably, it is more than 35m 2 The N2SA of carbon black is measured by the above-mentioned measuring method.
[0102] <Other filling materials> The rubber composition constituting the sidewall according to the present invention may contain fillers other than silica and carbon black. Such fillers are not particularly limited and may be materials known in the rubber field, such as inorganic fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica.
[0103] <Filler content> The content of silica (total amount of silica) is 20 parts by mass or more, more preferably more than 23 parts by mass, even more preferably more than 26 parts by mass, and even more preferably more than 29 parts by mass, based on 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 60 parts by mass, more preferably less than 50 parts by mass, and even more preferably less than 40 parts by mass. By being within the above range, it is believed that the rubber is adequately reinforced, the silica surfaces become more easily slippery against each other, the elongation at break (EB) is improved, and the crack resistance performance can be easily improved.
[0104] When carbon black is contained, the content per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 5 parts by mass, and even more preferably 10 parts by mass or more, from the viewpoint of obtaining reinforcement and preventing deterioration due to ultraviolet rays. Also, from the viewpoint of obtaining flexibility and relieving stress, the content is preferably less than 90 parts by mass, more preferably less than 80 parts by mass, even more preferably less than 70 parts by mass, even more preferably 60 parts by mass or less, even more preferably less than 40 parts by mass, and even more preferably less than 30 parts by mass.
[0105] From the viewpoint of the effects of the present invention, the content of the filler (total content of the fillers) is preferably more than 20 parts by mass, more preferably more than 30 parts by mass, and even more preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is preferably less than 200 parts by mass, more preferably less than 150 parts by mass, and even more preferably less than 100 parts by mass, and may be, for example, less than 50 parts by mass.
[0106] ≪Formula (3)≫ When the rubber composition constituting the sidewall according to the present invention contains carbon black, the content (parts by mass) of silica per 100 parts by mass of the rubber component is A SIL and the carbon black content (parts by mass) A CB It is preferable that the following relationship is satisfied: (3) A CB / A SIL <= 1
[0107] The value of the right side of formula (3) is preferably 0.90, more preferably 0.80, even more preferably 0.70, even more preferably 0.60, and even more preferably 0.50. CB / A SIL The lower limit may be 0.00, 0.10, or 0.20.
[0108] <Silane coupling agent> Generally, when silica is used, a silane coupling agent may be used in combination, but in the present invention, it is acceptable to use silica but not to substantially contain a silane coupling agent. Here, "substantially not containing" means that, even if it is contained, it is contained only to the extent that it does not affect the effects of the present invention. The silane coupling agent is not particularly limited, but examples thereof include sulfide-based silane coupling agents such as bis(3-triethoxysilylpropyl) disulfide and bis(3-triethoxysilylpropyl) tetrasulfide; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, and NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive; vinyl-based silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminopropyltriethoxy ... Examples of the silane coupling agents include amino-based silane coupling agents such as ethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chloro-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane, etc., and sulfide-based silane coupling agents and / or mercapto-based silane coupling agents are preferred, and mercapto-based silane coupling agents are particularly preferred. These silane coupling agents may be used alone or in combination of two or more.
[0109] When containing silane coupling agent, the content (when using multiple silane coupling agents, the total amount) relative to 100 parts by mass of silica is preferably less than 20 parts by mass, more preferably less than 15 parts by mass, even more preferably less than 12 parts by mass, even more preferably less than 9 parts by mass, and even more preferably less than 7 parts by mass, from the viewpoint of cost performance. Note that, from the viewpoint of improving the dispersibility of silica, the content of silane coupling agent is preferably more than 1 part by mass, more preferably more than 3 parts by mass, and even more preferably more than 5 parts by mass.
[0110] (Other compounding agents) The rubber composition constituting the sidewall according to the present invention may contain other compounding ingredients such as plasticizers, waxes, antioxidants, stearic acid, zinc oxide, vulcanizing agents, and vulcanization accelerators.
[0111] (Plasticizer) A plasticizer is a material that imparts plasticity to a rubber component, and is a concept that includes both plasticizers that are liquid (liquid state) at room temperature (25°C) and plasticizers that are solid at room temperature (25°C). Examples of plasticizers include resins, oils, liquid polymers, and ester-based plasticizers. A single type of plasticizer may be used alone, or two or more types may be used in combination.
[0112] <Resin> The rubber composition constituting the sidewall according to the present invention may contain a resin. Examples of the resin include petroleum resins, terpene resins, rosin resins, and phenol resins commonly used in the tire industry. These resin components may be used alone or in combination of two or more.
[0113] [Petroleum resin] Examples of the petroleum resin include C5 petroleum resin, aromatic petroleum resin, and C5C9 petroleum resin.
[0114] C5 petroleum resin refers to a resin obtained by polymerizing a C5 fraction, and may be a hydrogenated or modified resin. Examples of C5 fractions include petroleum fractions having 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. As a C5 petroleum resin, dicyclopentadiene resin (DCPD resin) is preferably used.
[0115] The aromatic petroleum resin refers to a resin obtained by polymerizing a C9 fraction, and may be a hydrogenated or modified resin. Examples of the C9 fraction include petroleum fractions having 8 to 10 carbon atoms, such as vinyltoluene, alkylstyrene, indene, and methylindene. Specific examples of aromatic petroleum resins that can be suitably used include coumarone-indene resins, coumarone resins, indene resins, and aromatic vinyl resins. As the aromatic vinyl resin, a homopolymer of α-methylstyrene or styrene or a copolymer of α-methylstyrene and styrene is preferred, and a copolymer of α-methylstyrene and styrene is more preferred, because they are economical, easy to process, and have excellent heat generation properties. As the aromatic vinyl resin, for example, commercially available products from Kraton, Eastman Chemical, etc. can be used.
[0116] The C5C9 petroleum resin refers to a resin obtained by copolymerizing the C5 fraction and the C9 fraction, and may be a hydrogenated or modified resin. Examples of the C5 fraction and the C9 fraction include the petroleum fractions mentioned above. As the C5C9 petroleum resin, for example, those commercially available from Tosoh Corporation, LUHUA, etc. can be used.
[0117] [Terpene resin] Examples of the terpene resin include polyterpene resins consisting of at least one selected from terpene compounds such as α-pinene, β-pinene, limonene, and dipentene; aromatic modified terpene resins made from the terpene compounds and aromatic compounds; terpene phenolic resins made from terpene compounds and phenolic compounds; and terpene resins obtained by subjecting these terpene resins to hydrogenation treatment (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, and divinyltoluene. Examples of phenolic compounds that are raw materials for terpene phenolic resins include phenol, bisphenol A, cresol, and xylenol.
[0118] [Rosin-based resin] The rosin-based resin is not particularly limited, but examples thereof include natural rosin resin and rosin-modified resins obtained by modifying rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.
[0119] [Phenol-based resin] The phenol-based resin is not particularly limited, but examples thereof include phenol formaldehyde resin, alkylphenol formaldehyde resin, alkylphenol acetylene resin, and oil-modified phenol formaldehyde resin.
[0120] [Resin content] The content of the resin component per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 3 parts by mass, even more preferably more than 4 parts by mass, and even more preferably 5 parts by mass or more. The content of the resin component is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, and even more preferably less than 20 parts by mass.
[0121] <Oil> Examples of the oil include process oil, vegetable oil, and animal oil. Examples of the process oil include paraffin-based process oil, naphthenic process oil, and aromatic process oil. In addition, a process oil having a low content of polycyclic aromatic compound (PCA) compounds can be used as an environmental measure. Examples of the low PCA content process oil include light extract solvate (MES), treated distillate aromatic extract (TDAE), and heavy naphthenic oil. In addition, from the viewpoint of life cycle assessment, waste oil after being used in rubber mixers and engines, or waste edible oil used in restaurants may be refined and used. The oil may be used alone or in combination of two or more types.
[0122] <Liquid polymer> The liquid polymer is not particularly limited as long as it is a polymer that is in a liquid state at room temperature (25° C.), and examples thereof include liquid butadiene rubber (liquid BR), liquid styrene butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene isoprene rubber (liquid SIR), liquid farnesene rubber, etc. The liquid polymer may be used alone or in combination of two or more kinds.
[0123] <Ester-based plasticizers> Examples of ester-based plasticizers include dibutyl adipate (DBA), diisobutyl adipate (DIBA), dioctyl adipate (DOA), di-2-ethylhexyl azelate (DOZ), dibutyl sebacate (DBS), diisononyl adipate (DINA), diethyl phthalate (DEP), dioctyl phthalate (DOP), diundecyl phthalate (DUP), dibutyl phthalate (DBP), dioctyl sebacate (DOS), tributyl phosphate (TBP), trioctyl phosphate (TOP), triethyl phosphate (TEP), trimethyl phosphate (TMP), thymidine triphosphate (TTP), tricresyl phosphate (TCP), trixylenyl phosphate (TXP), etc. The ester-based plasticizers may be used alone or in combination of two or more.
[0124] <Content of plasticizers other than resin> When a plasticizer other than resin is contained, the content (total amount when a plurality of plasticizers are used) per 100 parts by mass of the rubber component is preferably more than 1 part by mass, more preferably more than 2 parts by mass, and even more preferably more than 3 parts by mass. The content of the plasticizer is preferably less than 50 parts by mass, more preferably less than 40 parts by mass, and even more preferably less than 30 parts by mass.
[0125] <Wax> The wax is not particularly limited, and any wax commonly used in the tire industry can be suitably used, such as petroleum wax, mineral wax, and synthetic wax. Of these, petroleum wax is preferred. Petroleum wax includes, for example, paraffin wax, microcrystalline wax, and selected special waxes thereof, and paraffin wax is preferred. Waxes that can be used include, for example, those manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Paramelt Co., Ltd., and the like. Waxes can be used alone or in combination of two or more kinds.
[0126] When the wax is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.3 parts by mass, more preferably more than 0.5 parts by mass, and even more preferably 1.0 part by mass or more, while the content is preferably less than 4.0 parts by mass, more preferably less than 3.0 parts by mass, and even more preferably less than 2.0 parts by mass.
[0127] <Anti-aging agent> The antiaging agent is not particularly limited, and any of those commonly used in the tire industry can be suitably used. Examples of the antiaging agent include quinoline-based antiaging agents, quinone-based antiaging agents, phenol-based antiaging agents, phenylenediamine-based antiaging agents, and carbamic acid metal salts. Among them, phenylenediamine-based antiaging agents are preferred because they can more effectively improve the ozone resistance.
[0128] When an antioxidant is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 1.0 parts by mass, and even more preferably more than 2.0 parts by mass, while the content is preferably less than 7.0 parts by mass, more preferably less than 6.0 parts by mass, and even more preferably less than 5.0 parts by mass.
[0129] <Stearic acid> When stearic acid is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 0.7 parts by mass, and even more preferably more than 1.0 part by mass from the viewpoint of processability, while the content is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably less than 3 parts by mass from the viewpoint of vulcanization rate.
[0130] <Zinc oxide> When zinc oxide is contained, the content per 100 parts by mass of the rubber component is preferably more than 0.5 parts by mass, more preferably more than 0.7 parts by mass, and even more preferably more than 1 part by mass from the viewpoint of processability, while the content is preferably less than 10 parts by mass, more preferably less than 7 parts by mass, and even more preferably less than 5 parts by mass from the viewpoint of abrasion resistance.
[0131] <Vulcanizing agent> The vulcanizing agent is not particularly limited, and known vulcanizing agents can be used, such as organic peroxides, sulfur-based vulcanizing agents, resin vulcanizing agents, and metal oxides such as magnesium oxide. Among these, sulfur-based vulcanizing agents are preferred. As the sulfur-based vulcanizing agent, for example, sulfur donors such as sulfur and morpholine disulfide can be used. Among these, sulfur is preferably used. The vulcanizing agent can be used alone or in combination of two or more.
[0132] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur (oil-treated sulfur, special sulfur treated with a dispersant, master batch-type sulfur, etc.), and insoluble sulfur (oil-treated insoluble sulfur, etc.), and any of these can be used. Among these, powdered sulfur and insoluble sulfur are preferred. Examples of sulfur that can be used include those manufactured and sold by Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Co., Ltd., Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc.
[0133] When the vulcanizing agent is contained, the content relative to 100 parts by mass of the rubber component is preferably more than 0.4 parts by mass, more preferably more than 0.7 parts by mass, more preferably 1.0 parts by mass or more, and even more preferably more than 1.3 parts by mass. On the other hand, the content is preferably less than 6.0 parts by mass, more preferably less than 5.0 parts by mass, and even more preferably less than 3.0 parts by mass. When the content of the vulcanizing agent is within the above range, there is a tendency that an appropriate reinforcing effect is obtained, and the effect of the present invention tends to be better exhibited. In addition, when the vulcanizing agent contains a component other than sulfur, such as oil-treated sulfur, the content of the vulcanizing agent means the content of the sulfur component itself.
[0134] <Vulcanization accelerator> The vulcanization accelerator is not particularly limited, and known vulcanization accelerators can be used, such as sulfenamide-based, thiazole-based, thiuram-based, thiourea-based, guanidine-based, dithiocarbamic acid-based, aldehyde-amine-based or aldehyde-ammonia-based, imidazoline-based, or xanthate-based vulcanization accelerators. Among them, sulfenamide-based, thiuram-based, and guanidine-based are preferred, and sulfenamide-based are more preferred. As the vulcanization accelerator, for example, those manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Sanshin Chemical Industry Co., Ltd., etc. can be used. These vulcanization accelerators can be used alone or in combination of two or more.
[0135] Examples of sulfenamide vulcanization accelerators include N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), and N,N'-dicyclohexyl-2-benzothiazolylsulfenamide (DZ). Examples of thiuram vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide (TBzTD). Examples of guanidine vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-orthotolylguanidine, and orthotolylbiguanidine.
[0136] The content of the vulcanization accelerator relative to 100 parts by mass of the rubber component is preferably more than 0.3 parts by mass, more preferably more than 0.5 parts by mass, and even more preferably more than 0.6 parts by mass. On the other hand, the content is preferably less than 8.0 parts by mass, more preferably less than 5.0 parts by mass, and even more preferably less than 4.0 parts by mass. When the content of the vulcanization accelerator is within the above range, the breaking strength and elongation tend to be secured, and the effects of the present invention tend to be more favorably exhibited.
[0137] <Manufacturing> The rubber composition constituting the sidewall according to the present invention can be produced by a known method, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll or an internal kneader (Banbury mixer, kneader, etc.).
[0138] The kneading step includes, for example, a base kneading step in which compounding ingredients and additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, and a final kneading (F kneading) step in which the vulcanizing agent and the vulcanization accelerator are added to the kneaded product obtained in the base kneading step and kneaded. Furthermore, the base kneading step can be divided into a plurality of steps as desired.
[0139] The kneading conditions are not particularly limited, but examples include a method in which in the base kneading step, kneading is performed for 3 to 10 minutes at a discharge temperature of 150 to 170°C, and in the final kneading step, kneading is performed for 1 to 5 minutes at 70 to 110°C.
[0140] The tire of the present invention can be manufactured by a normal method using the above-mentioned rubber composition. That is, an unvulcanized rubber composition obtained by blending the above-mentioned components with the rubber component as necessary is extruded into the shape of a sidewall using an extruder equipped with a die of a predetermined shape, and the unvulcanized sidewall thus obtained is laminated together with other tire components on a tire building machine and molded by a normal method to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to manufacture a tire. The vulcanization conditions are not particularly limited, and examples thereof include a method of vulcanizing at 150 to 200°C for 10 to 30 minutes.
[0141] <Application> Examples of the tire include pneumatic tires and non-pneumatic tires. Among them, pneumatic tires are preferred. The tire can be used as a passenger car tire, a large passenger car tire, a large SUV tire, a heavy load tire such as a truck or a bus tire, a light truck tire, a two-wheeled vehicle tire, a racing tire (high performance tire), etc. Among them, it can be preferably used as a passenger car tire. Here, a passenger car tire is a tire that is assumed to be mounted on a four-wheeled vehicle and has a maximum load capacity WL of 1400 kg or less. EXAMPLES
[0142] The following are examples (working examples) that are considered to be preferable when carrying out the present invention, but the scope of the present invention is not limited to these working examples. Tires obtained according to each table were examined using the various chemicals shown below, and the results calculated based on the evaluation method described below are shown at the bottom of each table.
[0143] <Various chemicals> The chemicals used in the examples and comparative examples are summarized below.
[0144] IR rubber: Natural rubber (TSR20) BR: Ubepol BR150B (cis content 98% by mass, vinyl bond content 1% by mass) manufactured by Ube Industries, Ltd. SBR: HPR840 manufactured by JSR Corporation (styrene content: 10.0% by mass, vinyl bond content: 42.0% by mole) CB (Carbon Black) 1: Show Black N550 (manufactured by Cabot Japan Co., Ltd., N2SA: 42m 2 / g, average primary particle diameter 48nm) CB (Carbon Black) 2: Show Black N660 (manufactured by Cabot Japan Co., Ltd., N2SA: 35m 2 / g, average primary particle size 80nm) rCB (recovered carbon black): Carbon black obtained from the pyrolysis process of tires (ash content: 17% by mass) Silica 1: Ultrasil VN3 (N2SA175m) manufactured by Evonik Degussa 2 / g, average primary particle diameter: 17nm) Silica 2: Ultrasil 9100GR (N2SA235m) manufactured by Evonik Degussa 2 / g, average primary particle diameter: 15nm) Wax: Ozoace wax made by Nippon Seiro Co., Ltd. Antioxidant 1: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Antioxidant 2: Nocrac RD (poly(2,2,4-trimethyl-1,2-dihydroquinoline)) manufactured by Ouchi Shinko Chemical Co., Ltd. Oil: Diana Process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Stearic acid: Beads of stearic acid camellia manufactured by NOF Corporation Sulfur: SEIMI OT (insoluble sulfur containing 10% oil) manufactured by Nippon Kanretsu Kogyo Co., Ltd. Vulcanization accelerator: Noccela CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0145] <Production of Unvulcanized Rubber Composition> According to the compounding recipes shown in Tables 2-1 and 2-2 (collectively referred to simply as Table 2) and Tables 3-1 and 3-2 (collectively referred to simply as Table 3), chemicals other than sulfur and vulcanization accelerator are kneaded for 5 minutes using a 1.7 L closed Banbury mixer until the discharge temperature reaches 170°C, to obtain a kneaded product. Next, sulfur and vulcanization accelerator are added to the kneaded product obtained using a two-axis open roll, and the mixture is kneaded for 4 minutes until the temperature reaches 105°C, to obtain an unvulcanized rubber composition.
[0146] <Production of test tires> According to Tables 2 and 3, the obtained unvulcanized rubber composition is extruded into a sidewall shape using an extruder equipped with a nozzle of a predetermined shape, and the unvulcanized sidewall thus obtained is bonded together with other tire components on a tire building machine to form an unvulcanized tire. Each test tire (Tire 1: 265 / 70R18, Tire 2: 205 / 55R16) is manufactured by pressing the tire at 170°C for 12 minutes.
[0147] Furthermore, the microbumps on the outer surface of the sidewall are formed during press vulcanization using a mold equipped with a side plate having an engraving for forming the microbump engraved on the surface facing the microbump forming portion. The shapes of the microbumps A and B are as follows. The height h (mm) is the height of the microbump at the maximum tire width position, the height h1 (mm) is the height of the microbump at the outermost position in the tire radial direction, and the height h2 (mm) is the height of the microbump at the innermost position in the tire radial direction. When the value of h1 is greater than h, the height of the microbump gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and when the value of h2 is greater than h, the height of the microbump gradually increases from the maximum tire width position toward the inner side in the tire radial direction.
[0148] [Table 1]
[0149] <70℃ tanδ, 70℃ E*> A rubber test piece for viscoelasticity measurement, measuring 20 mm in length, 4 mm in width, and 1 mm in thickness, is cut from the inside of the sidewall of each test tire so that the long side is in the tire circumferential direction. For each rubber test piece, the loss tangent (70°C tan δ) and complex modulus of elasticity (70°C E*) (MPa) are measured in an extension deformation mode using a GABO Iplexer series under the following conditions: measurement temperature: 70°C, initial strain: 10%, dynamic strain: ±1%, frequency: 10 Hz.
[0150] <Crack resistance> The 265 / 70R18 test tire is mounted on a 18x8.5J rim, and the 205 / 55R16 test tire is mounted on a 16x6.5J rim. Each test tire is driven continuously for 40,000km using a drum (outer diameter: 1.7m) under the following conditions and a load is applied, and the total length of the cracks in the sidewall that have occurred after the drive is calculated. Load: 4.74kN Internal pressure: 290kPa Speed: 100km / h
[0151] Based on the total length of the above cracks, the crack resistance index of the standard mix is set at 100, and the crack resistance of each mix is expressed as an index using the following formula. The higher the index, the better the crack resistance. (Crack resistance performance index) = (crack length of standard mix) / (crack length of each mix) x 100
[0152] [Table 2]
[0153] [Table 3]
[0154] [Table 4]
[0155] [Table 5]
[0156] <Embodiment> The following are preferred embodiments.
[0157] [1] A tire having a pair of sidewalls, the rubber composition constituting the sidewall contains a rubber component and silica, and the content of the silica is 20 parts by mass or more, preferably more than 23 parts by mass, more preferably more than 26 parts by mass, and even more preferably more than 29 parts by mass, per 100 parts by mass of the rubber component; A tire in which, when the loss tangent (tan δ) of the rubber composition at 70°C is 70°C tan δ, the complex modulus of elasticity (MPa) of the rubber composition at 70°C is 70°C E*, and the thickness (mm) of the sidewall at the maximum width position of the tire is T, 70°C tan δ, 70°C E*, and T satisfy the following relationship, and the difference obtained by subtracting the value of the left side from the value of the right side of formula (1) is preferably greater than 0.010, more preferably greater than 0.020, even more preferably greater than 0.030, even more preferably greater than 0.040, even more preferably greater than 0.050, and even more preferably greater than 0.060, and the right side of formula (2) is preferably 8.0. (1) 70℃tanδ<0.0253×T+0.083 (2) 70℃E*≦10.0 [2] The tire according to [1], wherein a difference between the value on the left side and the value on the right side of formula (1) exceeds 0.070. [3] The tire according to [1] or [2], wherein the right side of formula (2) is 6.0, preferably 5.0, more preferably 4.7, even more preferably 4.1, even more preferably 4.0, and even more preferably 3.6. [4] The rubber composition contains carbon black, The content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is A SIL The carbon black content (parts by mass) is A CB Then, A SIL and A CBsatisfies the following relationship, and the value of the right side of formula (3) is preferably 0.90, more preferably 0.80, even more preferably 0.70, even more preferably 0.60, and still more preferably 0.50. (3) A CB / A SIL <= 1 [5] The tire according to any one of [1] to [4], wherein the rubber composition contains carbon black, and the carbon black contains recovered carbon black. [6] The tire according to any one of [1] to [5], wherein the silica contains silica having an average primary particle size of 16 nm or less, preferably less than 16 nm, more preferably 15 nm or less. [7] The tire according to any one of [1] to [6], wherein, when the tire weight (kg) of the tire is G and the maximum load capacity (kg) of the tire is WL, G and WL satisfy the following relationship, and preferably the right-hand side of formula (4) is 0.0170. (4) G / WL≦0.0180 [8] The tire according to [7], wherein the right side of formula (4) is 0.0165, preferably 0.0161. [9] The tire according to any one of [1] to [8], wherein at least one of the pair of sidewalls has a microridge forming portion having a plurality of microridges formed on an outer surface thereof.
[10] The tire according to [9], wherein the shape of the micro-protuberances is columnar, frustum or rib-like.
[11] The height of the micro-ridge is 0.03 mm or more and 0.50 mm or less, preferably 0.05 mm or more and 0.45 mm or less, more preferably 0.10 mm or more and 0.40 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction, and the micro-ridge forming portion is 10 mm 2 The tire according to [9] or
[10] , having an area of at least one of the above.
[12] The tire according to any one of [9] to
[11] , wherein the maximum width of the microprotrusions is 0.03 mm or more and 5.00 mm or less, preferably 0.05 mm or more and 3.00 mm or less, more preferably 0.10 mm or more and 1.00 mm or less, and even more preferably 0.10 mm or more and 0.50 mm or less.
[13] A tire described in any one of [9] to
[12] , wherein the height of the micro-protrusions gradually increases from the maximum tire width position toward the outer side in the tire radial direction, and gradually increases from the maximum tire width position toward the inner side in the tire radial direction. [Explanation of symbols]
[0158] Wt Tire section width Ht Tire section height Dt Tire outer diameter T Sidewall Thickness PW Maximum tire width position L normal 1. Outer surface of sidewall 2 Micro-protuberance 3 Micro-protuberance 4 Microprotuberance w Maximum width of the micro-ridge d Spacing of micro-ridges h Height of the micro-ridge
Claims
1. A tire having a pair of sidewalls, the rubber composition constituting the sidewall contains a rubber component and silica, and the content of the silica is 20 parts by mass or more per 100 parts by mass of the rubber component; A tire in which 70°C tan δ, 70°C E*, and T satisfy the following relationship, where 70°C tan δ is the loss tangent (tan δ) of the rubber composition at 70°C, 70°C E* is the complex modulus (MPa) of the rubber composition at 70°C, and T is the thickness (mm) of the sidewall at the maximum width position of the tire. (1) 70℃ tan δ<0.0253×T+0.083 (2) 70℃E*≦10.0
2. The tire according to claim 1 , wherein the difference between the value on the left side and the value on the right side of formula (1) is greater than 0.
070.
3. The tire according to claim 1 , wherein the right side of formula (2) is 6.
0.
4. The rubber composition contains carbon black, The content (parts by mass) of the silica relative to 100 parts by mass of the rubber component is A SIL The carbon black content (parts by mass) is A CB Then, A SIL and A CB The tire according to any one of claims 1 to 3, wherein the following relationship is satisfied: (3) A CB / A SIL ≦1
5. The tire according to any one of claims 1 to 3, wherein the rubber composition contains carbon black, and the carbon black contains recovered carbon black.
6. The tire according to any one of claims 1 to 3, wherein the silica contains silica having an average primary particle size of 16 nm or less.
7. The tire according to any one of claims 1 to 3, wherein G is a tire weight (kg) of the tire and WL is a maximum load capacity (kg), and G and WL satisfy the following relationship: (4) G / WL≦0.0180
8. The tire according to claim 7, wherein the right side of formula (4) is 0.0165.
9. 2. The tire according to claim 1, wherein at least one of the pair of sidewalls has a micro-ridge formation portion having a plurality of micro-ridges formed on an outer surface thereof.
10. 10. The tire of claim 9, wherein the micro-ridges are pillar-shaped, frustum-shaped or rib-shaped.
11. The micro-ridges have a height of 0.03 mm or more and 0.50 mm or less, and 20 or more are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge formation portion is 2 11. The tire according to claim 9 or 10, having an area of at least one of the above.
12. The tire according to claim 9 or 10, wherein the maximum width of the micro-ridges is 0.03 mm or more and 5.0 mm or less.
13. 11. The tire according to claim 9 or 10, wherein the height of the micro-bumps gradually increases from the maximum tire width position toward the outside in the tire radial direction, and gradually increases from the maximum tire width position toward the inside in the tire radial direction.
Citation Information
Patent Citations
Rubber composition for tire member, cap tread and sidewall, and pneumatic tire
JP2021014506A